Central Nervous System Involvement in ANCA-Associated Vasculitis: What Neurologists Need to Know - Zheng, Yang; Zhang, Yinxi; Cai, Mengting; Lai, Nanxi; Chen, Zhong; Ding, Meiping (Frontiers in Neurology, 2019)
Importance: Central nervous system (CNS) involvement in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is one of the few neurological disorders treatable with steroid and immunosuppressant. Yet AAV remains under-recognized among neurologists due to its myriad and evolving manifestations, causing diagnostic and treatment delays. Objective: To provide a comprehensive review of the CNS involvement in AAV, including the pathogenesis, clinical manifestations, ancillary investigations, differential diagnosis and treatment. Particular emphasis is placed on the clinical spectrum and diagnostic testing of AAV. Recent findings: AAV is a pauci-immune small-vessel vasculitis characterized by neutrophil-mediated vasculitis and granulomatousis. Hypertrophic pachymeninges is the most frequent CNS presentation. Cerebrovascular events, hypophysitis, posterior reversible encephalopathy syndrome (PRES) or isolated mass lesions may occur as well. Spinal cord is rarely involved. In addition, ear, nose and throat (ENT), kidney and lung involvement often accompany or precede the CNS manifestations. Positive ANCA testing is highly suggestive of the diagnosis, with each ANCA serotype representing different groups of AAV patients. Pathological evidence is the gold standard but not necessary. Once diagnosed, prompt initiation of induction therapy, including steroid and other immunosuppressants, can greatly mitigate the disease progression. Conclusions and relevance: Early recognition of AAV as the underlying cause for various CNS disorders is important for neurologists. Ancillary investigations especially the ANCA testing can provide useful information for diagnosis. Future studies are needed to better delineate the clinical spectrum of CNS involvement in AAV and the utility of ANCA serotype to classify those patients.